2008
DOI: 10.1097/gco.0b013e3282fdc6c3
|View full text |Cite
|
Sign up to set email alerts
|

Fertility drugs and risk of ovarian cancer: dispelling the myth

Abstract: As long as doubt persists, it might be advisable to reflect on a few clinical recommendations: identify high-risk infertile patients for ovarian cancer, investigate preexisting cancer before fertility treatment, inform patients regarding potential risks, obtain an informed consent, avoid exposure to long periods of ovulation induction cycles that are given before patients are referred for in-vitro fertilization and embryo transfer for women at greater risk and monitor women who have been treated with these dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
6
0
1
Order By: Relevance
“…Letzteres könnte bei zunehmender Pilleneinnahme weltweit sowohl die leicht abnehmende Inzidenz des invasiven Karzinoms als auch die relative Zunahme des Anteils der BOT an den Ovarialmalignomen erklären. Ein weiterer reproduktiver Faktor, der mit einem erhöhten Risiko für BOT (und auch invasives Karzinom) assoziiert wurde, ist Infertilität [99][100][101][102][103]. Die Daten zur Ovulationsstimulation mit Clomiphen und der Einsatz anderer Medikamente in der Fertilitätstherapie sind nicht einheitlich.…”
Section: Einleitung Epidemiologie Und Risikofaktorenunclassified
“…Letzteres könnte bei zunehmender Pilleneinnahme weltweit sowohl die leicht abnehmende Inzidenz des invasiven Karzinoms als auch die relative Zunahme des Anteils der BOT an den Ovarialmalignomen erklären. Ein weiterer reproduktiver Faktor, der mit einem erhöhten Risiko für BOT (und auch invasives Karzinom) assoziiert wurde, ist Infertilität [99][100][101][102][103]. Die Daten zur Ovulationsstimulation mit Clomiphen und der Einsatz anderer Medikamente in der Fertilitätstherapie sind nicht einheitlich.…”
Section: Einleitung Epidemiologie Und Risikofaktorenunclassified
“…The earlier published positive findings (Whittemore et al, 1992;Rossing et al, 1994;Akhmedkhanov et al, 2001b;Brinton et al, 2005;Brinton, 2007) were subject to several limitations, including small sample size, bias, imprecise information on drug exposure, namely type and duration of treatment and indications; furthermore, a lack of control for important confounding factors, such as causes of subfertility, parity or family history of cancer is noted. In addition, most studies tended to suffer from insufficient follow-up periods thereby preventing the accurate calculation of long-term treatment effect estimates (Land and Evers, 2003;Kashyap et al, 2004;Brinton et al, 2005;Mahdavi et al, 2006;Choi et al, 2007;Cetin et al, 2008;Jensen et al, 2008Jensen et al, , 2009aKällén, 2008;Zreik et al, 2008;Vlahos et al, 2010a;Impicciatore and Tiboni, 2011). Actually, the evidence regarding a tentative direct tumorigenic effect of fertility medication for ovarian stimulation is weak and controversial and relies mainly on in vitro studies (Huhtaniemi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Specific types of gynecological cancers have been traditionally associated with early age of menarche and late age of menopause (Vo and Carney, 2007), low parity, infertility (Stadel, 1975;Ron et al, 1987;Dahlgren et al, 1991;Brinton et al, 1992Brinton et al, , 2004Adami et al, 1994;Venn et al, 1995;Bristow and Karlan, 1996;Meirow and Schenker, 1996;Klip et al, 2000;Ness et al, 2002;Brinton, 2007;Cetin et al, 2008;Jensen et al, 2008Jensen et al, , 2009aKällén, 2008;Salehi et al, 2008;Zreik et al, 2008;Sueblinvong and Carney, 2009), tubal factor and unexplained infertility (Venn et al, 1999;Ness et al, 2002;Cetin et al, 2008), as well as ovulatory disorders, such as polycystic ovary syndrome (PCOS) (Escobedo et al, 1991;Rossing et al, 1994;Homburg, 1996;Schildkraut et al, 1996;Gregory et al, 2002), endometriosis (Brinton et al, 2004;Ness and Modugno, 2006;Vlahos et al, 2010b) and germline mutations in BRCA genes associated with occult primary ovarian insufficiency (Whittemore et al, 1992;Goshen et al, 1998;Brinton et al, 2004;Cetin et al, 2008;Källén, 2008;Zreik et al, 2008;Oktay et al, 2010;…”
Section: Introductionmentioning
confidence: 99%
“…There is not an increase of congenital anomalies or birth defects in the children conceived by women taking CC. Although some retrospective studies have reported an increased risk of ovarian cancer [22], overall there does not seem to be an increase in the incidence of ovarian or breast cancer in infertile women who have taken CC [23,24]. CC (50 mg) is taken once daily, beginning on day 3 or 5 of the cycle for 5 days.…”
Section: Intrauterine Insemination For Unexplained Infertilitymentioning
confidence: 99%